EEG Power and Functional Connectivity Correlates with Semantic Long-Term Memory Retrieval - Hanouneh, S. (Institute of Electrical and Electronics Engineers Inc., 2018)
In this paper, we investigated the relationships between EEG and semantic long-Term memory retrieval using spectral analysis and functional connectivity. We employed an EEG data set from a previous study, which was recorded from 34 healthy participants during a memory retrieval process. The data set consists of EEG collected during two tasks, a learning task, in which participants studied animated learning material, and a memory recall task, in which they recalled the learned information. We analyzed both EEG signals and behavioral responses. We conducted spectral analyses for the absolute power and relative power of EEG frequency bands, EEG coherence, absolute phase delay, and EEG amplitude asymmetry features. The delta-band EEG and theta-band absolute power were negatively correlated with task performance at frontal regions, while the alpha-band activity was positively correlated in frontal regions and negatively correlated in parietal and temporal sites. High-beta in the frontal lobe was positively correlated with memory recall score. EEG coherence was negatively correlated in the delta band at the fronto-parietal and fronto-central sites, and positively correlated in the gamma band at widespread regions, including all lobes. EEG phase delay showed the highest degree of connectivity in the delta and alpha bands at frontal sites, and was negatively correlated with memory recall score. The negative correlation in phase delay demonstrated the synchronization and positive correlation reflected the de-synchronization of electrode pairs during memory recollection in the delta and alpha frequencies. We concluded that neuronal networks producing low EEG frequencies at frontal regions and those producing high frequencies in widespread regions are active during the memory recollection process. Thus, semantic memory storage involves widespread neuronal networks across the brain. Â© 2013 IEEE.